MR Elastography of the Liver and the Spleen Using a Piezoelectric Driver, Single-Shot Wave-Field Acquisition, and Multifrequency Dual Parameter Reconstruction - Hirsch, Sebastian; Guo, Jing; Reiter, Rolf; Papazoglou, Sebastian; Kroencke, Thomas; Braun, Juergen; Sack, Ingolf (Magnetic resonance in medicine, 2014)
Purpose Viscoelastic properties of the liver are sensitive to fibrosis. This study proposes several modifications to existing magnetic resonance elastography (MRE) techniques to improve the accuracy of abdominal MRE. Methods The proposed method comprises the following steps: (i) wave generation by a nonmagnetic, piezoelectric driver suitable for integration into the patient table, (ii) fast single‐shot 3D wave‐field acquisition at four drive frequencies between 30 and 60 Hz, and (iii) single‐step postprocessing by a novel multifrequency dual parameter inversion of the wave equation. The method is tested in phantoms, healthy volunteers, and patients with portal hypertension and ascites. Results Spatial maps of magnitude and phase of the complex shear modulus were acquired within 6–8 min. These maps are not subject to bias from inversion‐related artifacts known from classic MRE. The spatially averaged modulus for healthy liver was 1.44 ± 0.23 kPa with ϕ = 0.492 ± 0.064. Both parameters were significantly higher in the spleen (2.29 ± 0.97 kPa, P = 0.015 and 0.749 ± 0.144, P = 6.58·10−5, respectively). Conclusion The proposed method provides abdominal images of viscoelasticity in a short time with spatial resolution comparable to conventional MR images and improved quality without being compromised by ascites. The new setup allows for the integration of abdominal MRE into the clinical workflow. Magn Reson Med 71:267–277, 2014. © 2013 Wiley Periodicals, Inc.